2021
DOI: 10.1186/s40816-021-00265-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of Malva verticillata against doxorubicin -induced toxicity in rats

Abstract: Background M. verticillata (Malvaceae) is a medicinal plant used in the treatment of wounds, boils, and liver injuries. The plant leaf extracts possess anti-inflammatory and antioxidant activities. Doxorubicin (DOX) is a potent chemotherapeutic agent used in the treatment of various cancers, but its clinical use is limited by acute and chronic cardiotoxicity. This study aims to evaluate the possible cardioprotective role of Malva verticillata against doxorubicin-induced cardiotoxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… Diabetic control (positive): STZ-induced Diabetic rats were fed a synthetic base diet. Group (1): STZ-induced diabetic rats fed a synthetic base diet plus an oral dose of Malva parviflora L. extract (500 mg/kg body weight/rat/day) ( Ibrahim et al., 2021 ). Group (2): STZ-induced diabetic rats fed a synthetic base diet plus an oral dose of Malva parviflora L. nano -formulation (500 mg/kg body weight/rat/day) ( Ibrahim et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Diabetic control (positive): STZ-induced Diabetic rats were fed a synthetic base diet. Group (1): STZ-induced diabetic rats fed a synthetic base diet plus an oral dose of Malva parviflora L. extract (500 mg/kg body weight/rat/day) ( Ibrahim et al., 2021 ). Group (2): STZ-induced diabetic rats fed a synthetic base diet plus an oral dose of Malva parviflora L. nano -formulation (500 mg/kg body weight/rat/day) ( Ibrahim et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Group (2): STZ-induced diabetic rats fed a synthetic base diet plus an oral dose of Malva parviflora L. nano -formulation (500 mg/kg body weight/rat/day) ( Ibrahim et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…To heal diabetic wounds, PUR/carboxymethylcellulose nanofibers containing Malva sylvestris extract are used. Malva extract as a modifier was incorporated in the PUR and different amounts of carboxymethyl cellulose blend and has been observed utility, antibacterial, and wound healing properties [46][47][48][49][50]. The obtained research results indicated that increasing the diameter of the nanofibers and decreasing the carboxymethyl cellulose concentration raised in progressive the freeing time up to 85 h. The application of natural extract in the polymer material extended the mechanical and thermal properties of nanofibers.…”
Section: Polyurethanes Modified With Antimicrobial Compoundsmentioning
confidence: 97%